2012
DOI: 10.1038/emboj.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin-SA1 deficiency drives aneuploidy and tumourigenesis in mice due to impaired replication of telomeres

Abstract: Cohesin is a protein complex originally identified for its role in sister chromatid cohesion, although increasing evidence portrays it also as a major organizer of interphase chromatin. Vertebrate cohesin consists of Smc1, Smc3, Rad21/Scc1 and either stromal antigen 1 (SA1) or SA2. To explore the functional specificity of these two versions of cohesin and their relevance for embryonic development and cancer, we generated a mouse model deficient for SA1. Complete ablation of SA1 results in embryonic lethality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 69 publications
14
196
0
1
Order By: Relevance
“…Similar results were obtained in mouse cells deleted for SA1 (Remeseiro et al, 2012a). The need for specialized cohesion at telomeres is likely due to the repetitive G-rich structure, which poses problems for replication fork progression, leading to nicks and gaps that must be repaired prior to mitosis.…”
Section: Introductionsupporting
confidence: 73%
“…Similar results were obtained in mouse cells deleted for SA1 (Remeseiro et al, 2012a). The need for specialized cohesion at telomeres is likely due to the repetitive G-rich structure, which poses problems for replication fork progression, leading to nicks and gaps that must be repaired prior to mitosis.…”
Section: Introductionsupporting
confidence: 73%
“…Although 90% of solid tumors display whole-chromosome aneuploidy, it is not clear what role aneuploidy plays in transformation and cancer progression. In mouse models, chromosomal instability (CIN) can both instigate and inhibit tumorigenesis (33,(38)(39)(40)(41). In human patients, CIN in tumor cells is generally associated with aggressive disease (42), although in some contexts high levels of CIN actually correlate with improved prognosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Davoli et al study (Davoli et al, 2010), the endoreplication observed in the study by Pampalona et al (Pampalona et al, 2012) requires aberrant (short) telomeres, but also requires loss of the transcriptional repressor Rb, rather than loss of p53. Telomere replication defects also contribute to endoreplication through failed chromosome segregation in mouse embryonic fibroblasts lacking the chromosome cohesion component SA1 (Remeseiro et al, 2012). These telomere studies provide potential mechanistic insight into how some animal tissues respond to DNA damage.…”
Section: Genome Instability Promotes Endoreplicationmentioning
confidence: 99%